Understanding Pilgrimage Tourist Satisfaction: Determinants, Revisit Intention, and Word of Mouth in Java Indonesia - Dadang Husen Sobana; Vemy Suci Asih; Setiawan Setiawan; Elsa Yulandri (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2026)
Purpose: This study examines the determinants of pilgrimage tourist satisfaction and analyzes its implications for revisit intention and Word-of-Mouth (WoM). Specifically, it explores the roles of religiosity, place attachment, destination image, emotional experience, and worldly desires in shaping satisfaction within pilgrimage tourism destinations.Design/Methodology: A quantitative approach was employed using a cross-sectional survey design. Data were collected through a questionnaire survey conducted from 240 pilgrims visiting major Wali Songo pilgrimage destinations in Java, Indonesia. The proposed relationships among variables were tested using variance-based Structural Equation Modeling (SEM-PLS).Findings: The results show that destination image and worldly desires have a positive and significant effect on tourist satisfaction. In contrast, religiosity, place attachment, and emotional experience do not significantly influence satisfaction. Tourist satisfaction positively affects revisit intention but does not directly influence WoM. Revisit intention, however, demonstrates a positive effect on Word of Mouth (WoM).Practical Implications: These findings suggest that pilgrimage destination managers should focus on strengthening destination image and addressing visitors’ experiential and personal motivations to enhance satisfaction and encourage repeat visits. Strategies that emphasize revisit intention may be more effective in generating positive WoM than relying solely on satisfaction-based recommendations.Originality/Value: This study contributes to pilgrimage tourism literature by positioning worldly desires as a key determinant of tourist satisfaction, offering a more comprehensive understanding of pilgrim motivation beyond purely spiritual dimensions. The results provide empirical insights for developing experience-oriented and sustainable pilgrimage tourism management strategies.